EXACERBATION OF INEQUITIES DURING COVID-19: ETHICAL IMPLICATIONS FOR SOCIAL WORKERS - Weinberg, Merlinda (Canadian Social Work Review / Revue canadienne de service social)

(untitled) (Canadian Association for Social Work Education / Association canadienne pour la formation en travail social (CASWE-ACFTS), 2020)
COVID -19 has upended the known world and the profession of social work has been on the frontlines responding to the human suffering. A global research study was conducted to survey the ethical challenges faced by social workers during the pandemic. This paper explores one theme from the Canadian data, namely the ethical implications for social workers arising from the greater risks, hardships, and inequities for those most marginalized in our society. Two populations of service users will be utilized as examples of the ethical dimensions of the problem: the elderly and those who are Indigenous.